The relationship between mindful self-care and maternal-fetal attachment in pregnant women: the parallel mediating effects of positive and negative affect - Xu, Lika; Sun, Xueyi; Liu, Yifan; Chen, Yujie; Wang, Caiyun; Li, Ting; Liu, Hanjiao; Wei, Junfan; Li, Meng (Frontiers in Psychiatry, 2025)
ObjectiveTo investigate the relationship between mindful self-care and maternal-fetal attachment (MFA) and parallel mediating effects of positive and negative affect among pregnant women.MethodsA cross-sectional survey using convenience sampling from June 2025 to July 2025 in six tertiary hospitals in Henan and Guangdong province. A total of 351 pregnant women were recruited and a questionnaire including socio-demographic characteristics, positive and negative affect scale and maternal antenatal attachment scale was used. Descriptive statistics, t-tests, one-way ANOVA, Harman’s single-factor test, Pearson correlation analysis, and parallel mediation analysis were conducted.ResultsCorrelation analysis showed that mindful self-care, positive affect, negative affect and MFA were all significantly correlated with each other, respectively. Once positive affect and negative affect were included as mediators, the direct effect of mindful self-care on MFA was no longer significant, suggesting that positive affect and negative affect fully mediated the relationship between mindful self-care and MFA.ConclusionPositive and negative affect play parallel mediating roles in the relationship between mindful self-care and MFA, emphasizing the critical role of emotion regulation in developing prenatal MFA and underscore the important value of mindful self-care as a psychological resource during pregnancy, which provides new perspectives for future theoretical models and intervention designs.